First autochthone case of sporotrichosis by Sporothrix globosa in Portugal - Oliveira, Manoel Marques Evangelista de (2014)
This research was supported by FEDER funds through the Operational Programme COMPETE and national funds through Fundação para a Ciência e Tecnologia, in the scope of project PEst-C/BIA/UI4050/2011, and by FAPERJ/Rio de Janeiro, Brazil (grant proc. E-26/110.619/2012) R. M. Z-O. is supported in part by CNPq 350338/2000-0 and FAPERJ E-26/103.157/2011. M. M. E. O. was supported by a grant from CAPES 2445/11-5.